Ethernet's high-wire act [new IEEE standard]. - Cherry, S. (IEEE spectrum)
The local- and metropolitan-area networking committee of the IEEE 802.1 working group has been tasked to develop a standard that could ensure the high quality of service needed to transmit streaming multimedia over a wide-area Ethernet network that covers an entire city. The new standard hopes to make possible dramatic improvements in services such as Internet-based television. Once the standard is in place, costs are expected to drop for carriers, which can pass those savings on to the users of their high-speed services.